(untitled) - International Labour Organization in Vietnam (ILO) (Vietnam, 2007)
This research build on a study on the demand for and the supply of risk management financial services in Vietnam carried out by the ILO/MOLISA microfinance project in 2003
Keywords: Microinsurance,Bảo hiểm vi mô; Low income,Thu nhập thấp; Vietnam,Việt Nam